(untitled) (Journey for Sustainable Development and Peace Journal, 2023)
Introduction: The role of antioxidant-rich nutritious foods like fruits and vegetables in preventing non-communicable diseases is critical. It helps to neutralize oxidative and nitrosative stresses. The nitrosative stresses are harmful to health and antioxidant-enhancing control of such stresses. Objective: The study aims to explore the benefit of dietary antioxidants such as fruits and vegetables that helps to reduce oxidative and nitrosative stress levels. A high level of oxidative and nitrosative stress levels results in non-communicable disease and depression. Methods: Both primary and secondary data are used for the study. Literature related to antioxidant foods is intensively reviewed. Primary data are collected through structured questionnaires with 68 numbers of respondents in Lalitpur metropolitan city, ward 28 in order to know the usage and knowledge of antioxidant practices at the ground level. There were 68 respondents with 88% of females and 12% of males between 20 and 60 years of age. The food frequency questionnaire was used to collect data. Findings & Discussion: Nepal is rich in antioxidant foods, however, only a small population has access to it. Likewise, many people are unaware of its proper consumption or usage. The consumption of fruits in Nepal is poor; only 2.7 and 1.6 in urban and rural respectively weekly based which is poor and below than average. From the food frequency table of primary data, it is shown that the consumption of fruits once a day is only by 9 among 68 respondents which is poor and below average. The finding suggests that dietary antioxidant source fruit intake is used by small numbers and chances of non-communicable diseases may be high. Conclusions: There has been a practice of dietary antioxidants, though on a small scale and a majority of them were unconscious of the proper use of dietary antioxidants.